Paradigm Shift in Lecturing Towards Students in the Post-Pandemic Context: Challenges and Ethical Implications - RAFLISYAH, Muhammad; YASMIN, Indyra; LATIFA, Novia Ayu (PT Batara Swastika Harati, 2023)
During online learning in Indonesia, various issues related to learner ethics were found. According to the Human Capital Index 2020, the knowledge of students in Indonesia who are expected to complete 12 years of schooling due to the pandemic is equivalent to only 7 years of learning. Moving on to the university level causes a decrease in the social ethics possessed by each student due to the pandemic, because they need to have a good learning process and knowledge of ethical implications. This research examines the challenges and ethical implications in the post-pandemic context. This research dissects the factors that cause students' paradigm shifts in post-pandemic lectures. In this study, researchers will conduct a case study on the paradigm shift in lectures in the academic community of Yogyakarta State University. The research sample used a purposive sampling technique, so researchers used samples of students and lecturers at the Faculty of Social, Legal, and Political Sciences, Yogyakarta State University. The results of this study are expected to be study material and a reference source for students and lecturers to address the ethical implications in the context of post-pandemic learning, as well as a wise reflection on responding to changes in the previous educational period.